ISRA-Bloomberg Sharīʿah stock screening and income cleansing methodologies: a conceptual paper - Ashraf Md. Hashim; Farrukh Habib; Ziyaat Isaacs; Mohamed Anouar Gadhoum (ISRA International Journal of Islamic Finance, 2017)
Purpose: The purpose of this paper is to explain and critically analyse the Sharīʿah screening criteria and cleansing process for income generated from stocks with a special focus on a newly developed ISRA-Bloomberg methodology. Design/methodology/approach: The paper focuses on the methodology of ISRA-Bloomberg in terms of Sharīʿah screening of stocks and the income cleansing process. To achieve this objective, this paper adopts a descriptive approach. Findings: The methodology of ISRA-Bloomberg is unique in terms of its criterion for screening stocks, the cleansing process and coverage of the universe of stocks. It facilitates the investors by offering a novel colour-coding scheme to indicate the Sharīʿah compliance of a stock. It also provides the exact ratios of the Sharīʿah-compliance criteria to the investors so they can closely observe changes in the trend of ratios and decide beforehand whether or not a company is likely to remain within the Sharīʿah-compliant list. The paper further discusses the issues in the screening and cleansing practices faced by the industry. Research limitations/implications: This research is limited to the criteria of screening and income purification of stocks which have been used by ISRA-Bloomberg from a Sharīʿah perspective. Practical/implications: The robust screening criteria and comprehensive analysis of the stocks will enhance the confidence of Islamic capital market participants. The investors, regulators and index providers will be equally able to benefit from this initiative. Originality/value: The paper focuses on the recently established methodology of ISRA-Bloomberg, which has not been discussed in the literature until now. The methodology, because of its exceptionality, may add a new dimension to Sharīʿah screening and cleansing of stocks.
Keywords: 330; Islamic finance; Sharīʿah-compliant shares; Islamic equity; Screening criteria; Income purification